Tribal education in India: an examination of cultural imposition and inequality - Mukherjee, Anirban (Kansas State University, 2009)
ABSTRACT This qualitative research study explores the cultural dissonance promoted in Indian tribal students by participation in the mainstream Indian educational system and the changes this has brought to their lives. Previous studies have tried to analyze the problem from four theoretical perspectives: biological interpretation, the socio-economic perspective, inter-colonization theory, and the cultural reproduction perspective. This study examines the applicability of these perspectives in analyzing the participation of Indian tribal students in the Indian education system. It attempts to identify elements that are incompatible with tribal culture, examine the difference in educational achievement between the tribal elites and their downtrodden counterparts, assess the social standing of the tribal graduates, and examine teachers’ conception of tribal students. The study used a non-experimental, cross-sectional research design with the main tools of data collection being observation and personal interviews. The study was conducted on the Santal, Birhor, Kharia and Lodha tribes located in Bankura, Birbhum, Puruliya, and Paschim Medinipur districts of the state of West Bengal in India. Personal interviews were conducted with tribal students, graduates, parents, teachers, and principals of tribal schools. The research revealed that the modern education system makes little attempt to address cultural specificities in designing education policies for tribal students which results in the development of a negative self-image. Moreover, although claimed to be free by the Indian government, achieving success in the education system involves subsidiary costs like private tution which represents an obstacle for poverty stricken tribal families. The problem is further complicated due to the unempathetic attitudes and beliefs of teachers and the ill-conceived developmental policies designed by educational planners that fail to incorporate curricular elements compatible with tribal culture.
Keywords: Tribes; Education; India; Cultural Imposition; Inequality; Sociology, General (0626)